Research of resistance of pipe hydraulics untreated water line system (PVC) before and after mechanical cleaning – case study - Koral, Wojciech (Instal, 2024)
The paper shows the results of research on resistance coefficient of untreated water line made of PVC before and after its mechanical cleaning, indicating that automatic air vent can be the cause of iron residue inside pipes.